Evaluation of patients’ experiences at different stages of the intravitreal injection procedure – what can be improved? - Tailor R (Dove Medical Press, 2011)
Rajen Tailor, Rebecca Beasley, Yit Yang, Niro NarendranWolverhampton and Midland Counties Eye Infirmary, New Cross Hospital, Wolverhampton, UKIntroduction: Intravitreal injection of ranibizumab has become one of the most commonly performed ophthalmic procedures. It is timely to conduct an evaluation of the injection procedure from the patient’s perspective so as to determine ways to improve patient experience. The purpose of this study was to quantitatively describe patients’ experiences of the different stages of the intravitreal injection procedure and provide suggestions for improvement.Method: Following intravitreal injection, patients were administered a questionnaire to score the distress felt for each of ten parts of the whole injection process from the initial waiting to the final instillation of topical antibiotic at the end. A score of higher than 4 was regarded as significantly unpleasant. The proportion of scores above 4 for each step was used to evaluate the relative distress experienced by patients for the different parts of the procedure.Results: A total of 42 patients were surveyed. The step with the highest percentage of patients scoring more than 4 was the injection step (19%). However, cumulatively, the steps relating to the application of the drape, the speculum, and the removal of drape accounted for 53% of scores greater than 4.Conclusion: There is considerable variation in how patients tolerate different stages of the injection procedure. The needle entry was the most unpleasant step followed by the draping steps cumulatively. Use of subconjunctival anesthesia, a perforated drape, and alternative lid exclusion devices may help to improve the patient’s tolerability of the procedure and experience.Keywords: ranibizumab, patient experience, age-related macular degeneration